IMPLEMENTASI AJARAN PARĀŚARA DHARMAŚĀSTRA PASCA REFORMASI DALAM MEMPERTAHANKAN ŚRADDHĀ DAN BHAKTI UMAT HINDU - Ketut Budiawan (Jurnal PASUPATI, 2013)
Abstract In post-reform era, people change their way of thinking from collectivism to individualistic by the considering values of human rights. There is the controversy between them and rule ignorance. For instance, some people think that they have rights to do anything they want and they often neglect the rules in the society. To maintain the rules in creating the harmonious and peaceful life, shanti, Hindu has Parāśara Dharmaśāstra. The research questions are: 1) How is the Parāśara Dharmaśāstra concept in Hindu?, 2) How is the implementation of Parāśara Dharmaśāstra in post-reform era in order to keep Sradha and Bhakti for Hindu people that it concerns on Hindu fundamental framework?, 3) How is the implementation of Parāśara Dharmaśāstra in post-reform era in order to keep Sradha and Bhakti for Hindu people that it emphasizes on Tri Hita Karana concept. Parāśara Dharmaśāstra concerns on Tattva that is based on five beliefs, Panca Sradha consisiting of WidhiTattva, believe in God (Brahman), AtmaTattva, believe in Atman (the true self of an individual or the essence of an individual), Karmaphala Tattva, believe in karma (natural law of cause and effect), Punarbawa Tattva, believe in rebirth process (reincarnation), and MoksaTattva, believe that Atman and Brahman are integrated. Ethic is the reciprocal process to build the individual and social life harmoniously. Acarais the customary law including the Hindu holy rituals consisting PancaYajna and Tri Hita Karana as the theory in order to make the bliss. The implementation of Parāśara Dharmaśāstra that focuses on Hindu fundamental frameworkand Tri Hita Karanaaims to guide human beings as the individual and social people in gaining the awareness to reach the freedom in order to increase the quality of humanism and social life.  Key words: Implementation, Hindu Law (Dharmaśastra), śraddhā and bhakti.